Endoscopic submucosal dissection of esophageal cancer using the Mucosectom2 device: a feasibility study - Kawahara, Yoshiro; Hori, Keisuke; Takenaka, Ryuta; Nasu, Junichiro; Kawano, Seiji; Kita, Masahide; Tsuzuki, Takao; Matsubara, Minoru; Kobayashi, Sayo; Okada, Hiroyuki; Yamamoto, Kazuhide (Endoscopy, 2013)
Background and study aims: Endoscopic submucosal dissection (ESD) is being increasingly used for superficial esophageal cancers. However, esophageal ESD is technically difficult, time consuming, and less safe compared with endoscopic mucosal resection (EMR). To perform ESD safely and more efficiently, various types of knives have been developed. This study compared the efficacy of our newly developed device, Mucosectom2, with that of conventional devices for esophageal ESD.Patients and methods: Between May 2007 and February 2011, ESD was performed for 172 esophageal lesions. Of these, 120 lesions were treated by conventional devices only, whereas 52 lesions were treated by conventional devices and the Mucosectom2. Procedure time, en bloc and R0 resection rates, and adverse events were retrospectively compared between the conventional and Mucosectom2 groups.Results: The median procedure time was 48.0 minutes in the conventional group and 21.5 minutes in the Mucosectom2 group; the procedure time was significantly shorter in the Mucosectom2 group than in the conventional group (P < 0.0001). The en bloc and R0 resection rates were lower in the conventional group than those in the Mucosectom2 group, although these differences were not significant. The rate of exposure of the muscle layer in the Mucosectom2 group was significantly lower than in the conventional group (P = 0.04). The rates of perforation and postoperative bleeding were not significantly different between the two groups.Conclusions: This feasibility study suggests that, compared with conventional ESD devices, the Mucosectom2 may decrease the time required for esophageal ESD. Although our groups appeared comparable, they were studied at different times. Endoscopic expertise and endoscope quality may have differed during these periods, thereby affecting the results of our study. A prospective trial is therefore required to confirm our results.